Mediterranean diet associated with lower frailty risk: A large cohort study of 21,643 women admitted to hospitals - Huifeng Zhang; Weimin Li; Youfa Wang; Yuanyuan Dong; Darren C. Greenwood; Laura J. Hardie; Janet E. Cade (Elsevier, 2024)
Background: Mediterranean diet is traditionally considered as a healthy dietary pattern, while its association with frailty has not been confirmed. This study investigated associations between Mediterranean diet and risk of frailty among women admitted to hospitals in England from an older-aged women's cohort study. Methods: A modified Mediterranean diet was evaluated from a validated 217-item food frequency questionnaire. Incident frailty was determined using a hospital frailty risk score based on linkage to Hospital Episode Statistics up to March 2019. Cox proportional hazard models were conducted to estimate hazard ratios (HR) and 95% confidence intervals (CI). Further subgroup analyses stratified by age and body mass index (BMI), and sensitivity analyses were additionally explored. Results: Over a mean follow-up of 13 years, there were 14,838 (68.6%) cases of frailty out of 21,643 individuals included in this study. Compared with low adherence to Mediterranean diet, moderate adherence was associated with 5% (HR = 0.95, 95%CI: 0.91, 0.99) lower risk of frailty, with high adherence associated with even lower risk (HR = 0.89, 95%CI: 0.85, 0.94). The magnitude of above associations remained consistent in subgroups stratified by age and BMI, except the association between moderate adherence and risk of frailty was attenuated in the ≥60-year (HR = 0.99, 95%CI: 0.93, 1.06) and the BMI > 24.9 kg/m2 (HR = 0.97, 95%CI: 0.91, 1.03) subgroups. Conclusions: Adherence to Mediterranean diet was associated with lower risk of frailty. The better the adherence, the greater the magnitude of the protective association. Older and overweight women may potentially benefit from greater adherence to the Mediterranean diet regarding frailty prevention.